2003
DOI: 10.4218/etrij.03.0101.0401
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate R&D Investment: An Empirical Study Comparing Korea's IT Industry with Its Non-IT Industry

Abstract: In our study, we extracted the market, finance, and government factors determining R&D investment of individual firms in the IT industry in Korea. We collected the financial data of 515 individual firms belonging to IT and non‐IT industries between 1980 and 1999 from the Korea Investors Service's database and investigated the empirical relationship between the factors using an ordinary regression model, a fixed effects model, and a random effects model. The main findings of our study are as follows: i) The Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 16 publications
3
26
1
2
Order By: Relevance
“…Yoo and Moon (2006) showed that R&D expenditure and R&D intensity of IT companies are higher than those of other companies in Korea. Lee and Hwang (2003) corroborates this finding.…”
Section: It and Venture Companiessupporting
confidence: 93%
See 2 more Smart Citations
“…Yoo and Moon (2006) showed that R&D expenditure and R&D intensity of IT companies are higher than those of other companies in Korea. Lee and Hwang (2003) corroborates this finding.…”
Section: It and Venture Companiessupporting
confidence: 93%
“…First, following the logic of the two famous Schumpeter hypotheses, one would expect large firms and firms that possess market power to be more active in R&D. The results from this analysis show that even though the first hypothesis, that larger firms are more active in R&D, is true in Korea, the other hypothesis, that firms that possess market power are more active in R&D, is not true in Korea. This result is consistent with other studies of Korea (Lee and Hwang, 2003;Yoo and Moon, 2006). However, some foreign studies (Kamien and Schwartz, 1982;Acs and Audretsch, 1988;Link and Rees, 1990;Bhattacharya and Bloch, 2004) showed that small firms were more active in R&D. Therefore, our results reveal the need to improve external conditions for stimulating small firms' R&D activities in Korea.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Empirical evidence [12,28,61] shows that firm size has a positive impact on R&D investment and firm performance. Hence, we expected a positive relationship between firm size and R&D investment and between firm size and firm performance.…”
Section: Variablesmentioning
confidence: 99%
“…proximity to academic centers and access to scientific and research infrastructure (Zucker et al, 1998), advanced technology and research equipment, including scientific-technological parks (Audretsch and Feldman, 1996;Pelle, Bober, and Lis, 2008) as well as access to sources of financing (Lerner, Shane, and Tsai, 2003;Brown, Fazzari, and Petersen, 2009;Gorodnichenko and Schnitzer, 2010;Aghion, Askenazy, Berman, Cette and Eymard, 2012). On the other hand, in terms of risk, the success of a research and development project is dependent on skill in applying for research grants (Almus and Czarnitzki, 2003;Becker and Pain, 2003;Lee and Hwang, 2003;Klette and Moen, 2012). Ali-Yrkkö (2004) calls attention to the fact that financing research and development through public funding can be seen as a lowering of the private cost of research and development projects thanks to which the undertaking of unprofitable projects may prove profitable.…”
Section: Commercialization Of Research Resultsmentioning
confidence: 99%